CD200 included in a 4‐marker modified Matutes score provides optimal sensitivity and specificity for the diagnosis of chronic lymphocytic leukaemia. Issue 3 (30th March 2018) - D'Arena, Giovanni; Vitale, Candida; Rossi, Giovanni; Coscia, Marta; Omedè, Paola; D'Auria, Fiorella; Statuto, Teodora; Valvano, Luciana; Ciolli, Stefania; Gilestro, Milena; Molica, Stefano; Bellesi, Silvia; et al.
Abstract: CD200, a transmembrane type Ia glycoprotein belonging to the immunoglobulin superfamily, has been shown to have a differential expression in B‐cell neoplasms. Here, we retrospectively assessed the diagnostic relevance of CD200 on 427 patients with B‐cell chronic neoplasms in leukemic phase (median age, 69 y; range, 35‐97 y). The final diagnosis based on the investigator's assessment was chronic lymphocytic leukaemia (CLL) in 75% of cases and non‐CLL in 25% of cases. Sensitivity and specificity for the diagnosis of CLL (vs non‐CLL) were calculated for the following markers: CD200, CD5, CD22, CD23, CD79b, FMC7, and SmIg. CD23 was the only marker without a statistically significant difference between the investigator assessment and the flowcytometric analysis. The other markers were unable—when individually evaluated—to discriminate between CLL and non‐CLL, requiring the integration into a scoring system. The modified score no. 1 (addition of CD200) showed superimposable sensitivity and specificity compared with the Matutes score. The substitution of CD79b (modified score no. 2), surface membrane immunoglobulins (SmIg) (modified score no. 3), and CD79b and FMC7 (modified score no. 4) with CD200 showed that only the modified score no. 4 had both higher sensitivity and higher specificity compared with standard Matutes score. In conclusion, this work defines a simplified score, compared with the classical Matutes score, for the differential diagnosis of chronic B‐cell leukaemia—which only requires 4 markers instead of 5 (CD5, CD23, CD200, and SmIg).